The knowledge regarding Breast Cancer, its risk factors, and screening practices among women from Islamabad, Pakistan - Sadia Yasir Khan, Sadaf Konain Ansari, Mohsin Khalid Qureshi, Tamkeen Nishat Jaffrey, Farah Rashid, Sadia Yasir Khan, Sadaf Konain Ansari, Mohsin Khalid Qureshi, Tamkeen Nishat Jaffrey, Farah Rashid (Journal of Rawalpindi Medical College, 2021)
Introduction: Breast Cancer is the rising Public health problem of the world. Pakistan is bearing a high disease burden not only in Asian countries but in the whole world. Pakistan ranks highest in Breast cancer and accounts for almost 34.6%of female cancers. The incidence of the disease in Asian countries is quite different from that in Western countries regarding age i.e. (40-50 years.) while (60-70 years) in Western countries. This study was based on assessing the knowledge regarding breast cancer, risk factors, and screening practices to determine the barriers in the path of the community to seek medical care. Materials and Methods: A cross-sectional study was done between October to December 2019 on 310 females participants of ages from 25 to 70 years, residents of Islamabad, the capital of Pakistan, and knowledge was assessed by applying a self-responding questionnaire. Results: Using SPSS version 23 and chi-square tests, the results showed that 87.7% of participants knew about the prevalence of Breast Cancer. Whereas, 90.3% of the females with the disease are not aware of their illness and show a strong association (p-value is less than 0.05) between knowledge regarding breast cancer and screening tests. Conclusion: The study concluded that 90% of socio-cultural barriers are in the path of access to medical facilities and 90% of participants believed that the non-availability of female doctors in health facilities is a big barrier to access to health. Access to medical facilities should be made easy by promoting health education and removing the fear of results, making small health facility units.